Pengembangan Model Pembelajaran Berbasis Matematika Realistik Berbantuan Geogebra Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa SMP Al Azhar Medan - Anggita Ulan Nasution; Edi Syahputra; Faiz Ahyaningsih (Mathematics Education Study Program, 2022)
This study aims to describe: 1) Find the validity, practicality, and effectiveness of realistic mathematics-based learning models developed to improve students' mathematical problem solving abilitiesl; and 2) Describe the improvement of students' mathematical problem-solving abilities using the developed learning tools. This research was conducted in two stages, namely the first stage of developing realistic mathematics-based learning tools using the 4-D development model, and the second stage testing realistic mathematics-based learning tools developed in grades VII-A and VII-B SMP Al Azhar Medan to see their effectiveness. From the results of trial I and trial II obtained: 1) the realistic mathematics-based learning model developed is effective, in terms of a) classical student learning completeness; b) achievement of learning objectives; and c) learning time; 2) The learning tools developed are practical to use; 3) Realistic mathematics-based learning tools developed can improve students' mathematical problem solving abilities; and 4) students' positive response to the activities and learning tools based on the developed realistic approach.